Medical treatment of open-angle glaucoma - Mohammed M Abdull; Dan Kiage; Fatima Kyari; Adunola Ogunro (Community Eye Health Journal, 2012)
Most guidelines that exist for the treatment of primary open-angle glaucoma (POAG) – such the National Institute for Health and Clinical Excellence (NICE) guidelines (page 47) – recommend medicine as initial therapy, though laser treatment may also play a role.None of these guidelines are based on research done in Africa, however, and there also is no evidence yet on the relative effectiveness of different glaucoma medications in African populations.For medicines to be effective at controlling POAG, they must be used every day for the remainder of the patient’s life.